DEVELOPMENT STRATEGY FOR KODIKLATAL ADMINISTRATIVE ASSISTANCE EDUCATION CENTERS TO IMPROVE THE QUALITY OF EDUCATIONAL RESULTS - Khristian Aden Gunawan; Mukhlis Mukhlis; Adi Bandono (Indonesian Naval Technology College STTAL, 2022)
The Indonesian National Armed Forces as the front line of national defense must implement policies that are inline with those conveyed by emphasizing on the ranks in order to carry out appropriate budgetary activities,especially those that are right on target for predetermined uses. The use of the budget must optimize the controlside of activities, the fulfillment of the procurement of goods and services as well as the maintenance of defenseequipment and the fulfillment of targeted supplies, as well as personnel management and updating of educationalinstitutions. The Center for Administrative Assistance Education, Kodiklatal is an instructive institution for the Navalforce which is the center for authoritative help instruction and has an imperative part in regulatory help instruction.The reason of this consider was to decide elective techniques for creating authoritative help instruction centers inarrange to move forward the quality of prepared warriors utilizing the SWOT strategy. The comes about of thedistinguishing proof are 15 (fifteen) inner variables with 8 (eight) quality variables and 7 (seven) shortcomingvariables, and 15 (fifteen) outside components with 8 (eight) opportunity components and 7 (seven) riskcomponents. By weighting all factors, the chosen methodology may be a strength-threat procedure which suggestsmaximizing the change of debilitating variables by utilizing qualities within the frame of concentric expansion, with5 (five) ST methodologies produced.Keywords : SWOT, education, administrative assistance